Rural Household’s Participation In Non-Farm Activities: The Case Of The Makuey District, Nuer Zone, Gambella Region, Ethiopia - Bor, Chuol; Sheikh Adan, Abdimajid (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Ethiopia is a farming nation where agriculture provides a living for a large portion of the inhabitants. Most rural households suffer from chronic poverty and food insecurity as a result of agriculture's deteriorating carrying capacity, land fragmentation, and low agricultural income. This makes rural households participate in non-farm activities to generate income to cope with these challenges. The study used a mixed study design. A step-by-step sampling procedure was used in this study in which the Makuey district was selected purposively, Puokuath and Bildak kebelle were selected at simple, random, and stratified sampling procedures were applied to select sample respondents. The study also employed a descriptive, inferential, and econometric model for data analysis. Based on the findings, only significant discrete variables were the gender, literacy level, and household credit access. Similarly, the significant continuous variables were market distance and household income. Furthermore, the main challenges facing rural households' participation in non-farm activities were bad infrastructure and negative cultural perception. The binary logit model result indicated that market distance, literacy level, and credit access were significant and negatively influenced rural households, while incomes and the gender of rural households were significant and positively influenced the rural household's involvement in non-farm activities. The study recommended that the regional and district governments should access infrastructure and create awareness about the benefits of non-farm activities.